Is It Really Mandatory to Harvest the Contralateral Saphenous Vein for Use in Repair of Traumatic Injuries?. (October 2018) - Reddy, Neil P.; Rowe, Vincent L.
Since the transition time in surgical technique of vascular repair to current civilian practice, the great saphenous vein (GSV) remains unarguably the preferred conduit for surgical reconstruction in the lower extremity. With qualities such as accessibility, expendability, and long-term durability, it is easy to understand the enthusiasm with using the GSV in arterial or venous vascular injuries. However, the question does arise whether these detailed benefits of the GSV warrant harvest from an uninjured limb for vascular reconstruction on an injured limb. For those ardent followers of surgical dogma, harvest of contralateral vein from the uninjured lower extremity traumatic vascular repair is mandated. Unfortunately, this principle is not supported by high-quality data and remains folklore at best.